2022
DOI: 10.1021/acs.est.1c05839
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation of Gill Epithelia in Fish Causes Increased Permeation of Petrogenic Polar Organic Chemicals via Disruption of Tight Junctions

Abstract: The epithelial cell layer that lines the gills of fish controls paracellular permeation of chemicals through tight junctions. The integrity of tight junctions can be affected by inflammation, which likely affects the bioavailability of chemicals.Here, the inflammation of the rainbow trout gill cell line RTgill-W1 was induced via exposure to bacterial lipopolysaccharides (LPS). Cells were then coexposed to extracts of oil sands processaffected water (OSPW), which contain complex mixtures of chemicals. After 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The liquid scintillation counting method without HPLC separation does not differentiate between parent compound and its biotransformation products so that the fraction measured in the cells reflects the sum of those. Interestingly, tetrachlorohydroquinone (THQ), a PCP biotransformation product, was found in low amounts in the exposure medium of PCP-exposed RTL-W1 cells (Pietsch et al, 2014), which has been confirmed in only one in vivo study with striped bass to date (Gates and Tjeerdema, 1993). In our measurements, this biotransformation product could not be detected.…”
Section: Mass Balances and Biotransformation Activitysupporting
confidence: 62%
See 1 more Smart Citation
“…The liquid scintillation counting method without HPLC separation does not differentiate between parent compound and its biotransformation products so that the fraction measured in the cells reflects the sum of those. Interestingly, tetrachlorohydroquinone (THQ), a PCP biotransformation product, was found in low amounts in the exposure medium of PCP-exposed RTL-W1 cells (Pietsch et al, 2014), which has been confirmed in only one in vivo study with striped bass to date (Gates and Tjeerdema, 1993). In our measurements, this biotransformation product could not be detected.…”
Section: Mass Balances and Biotransformation Activitysupporting
confidence: 62%
“…Therefore, cell surface sorption could not be considered in the presented partition exercise. Dedicated experiments and model approaches are needed to scrutinize the effect and contribution of each phenomenon to the overall observed accumulation in RTL-W1 cells (Schug et al, 2018;Stott et al, 2015;Minghetti et al, 2017;Chang et al, 2021;Fuchylo et al, 2022). In the larger context of IOC, it would be interesting to test a set of anionic organic compounds with similar molecular structures that resemble the structure of the cell membranes' phospholipids, such as surfactants (Ribbenstedt et al, 2022), or cationic organic compounds, which bear positive charges (Kierkegaard et al, 2021).…”
Section: Prediction Of Cell Internal Concentrationsmentioning
confidence: 99%
“…The epithelial cells of the gill serve as the first defense mechanism for fish against various environmental stresses, and its structural integrity is essential for preventing the infiltration of toxic substances and potential pathogens [ 1 , 30 , 36 ]. In the current study, microscopic observations of typical gill lesions are severe hyperplasia in the secondary lamella and apoptotic epithelial cells after DEL immersion, which were substantiated via HE and TUNEL assays.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the findings of our proteomic analysis revealed that immersion in DEL led to a reduction in the level of tight junction-related proteins, suggesting that posttranscriptional modifications play a role in the regulation of tight junctions. In fish, it has been demonstrated that exposure to chemicals leads to compromised tight junctions, resulting in heightened permeation across the gill epithelium, consequently elevating the toxicological risk [ 30 , 50 , 51 ]. As such, it is believed that the abnormal histological characteristics of gills are attributed to the destruction of gill barrier integrity, encompassing epitheliosis, mucus secretion, and epithelial cell junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation